The Effect of Positive Attitude in Encouraging Tourist Interest in Halal Tourism - Arevin, Ayat Taufik (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The halal tourism industry has grown rapidly and become an important sector in the global economy. This study aims to analyze the influence of perceptions of the concept and development of halal tourism on positive attitudes among the community, as well as how these positive attitudes affect tourist interest. Recognizing the importance of perceptions and attitudes in attracting tourists, this research examines these factors to provide in-depth insights into the dynamics of the halal tourism industry. This study employs a quantitative method with data collection techniques through surveys and questionnaires. The research sample consists of 273 respondents, including employees and managers of the halal tourism industry as well as visitors or tourists in the Yogyakarta City. The results show that positive perceptions of the concept and development of halal tourism significantly influence positive attitudes among the community. These positive attitudes, in turn, positively affect tourist interest in visiting halal tourism destinations. These findings underscore the importance of enhancing perceptions and positive attitudes among the community to attract more tourists and support the growth of the halal tourism industry.